2020
DOI: 10.11002/kjfp.2020.27.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics, antioxidant activities and acrylamide formation in cookies added with onion peel powder

Abstract: This study was conducted to investigate the quality characteristics, antioxidant activities and levels of acrylamide formation in cookies containing different amounts of onion peel powder. Onion peel powder was incorporated into the cookies at a level of 2-6% based on the total weight of wheat flour. The contents of moisture, ash, crude protein, total polyphenols, total flavonoids, and acrylamide content of cookies were determined, in addition to their antioxidant activities, pH values, loss rates, spread rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…TPC of wheat bread 30 and wheat cookies 25 with the addition of OSP was reported to be proportional to the amount of OSP at a rate of 1–5% and 2–6%, respectivelyand was similar to our functional wheat crackers.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…TPC of wheat bread 30 and wheat cookies 25 with the addition of OSP was reported to be proportional to the amount of OSP at a rate of 1–5% and 2–6%, respectivelyand was similar to our functional wheat crackers.…”
Section: Resultssupporting
confidence: 81%
“…The b* value of W.S1 was close to the control-W ( p > 0.05), and that of L.S1/L.E1/L.Q1 Wheat cookies with OSP were reported to have lower L* and b* values, and higher a* values. 25 Similar to our study, L*/b* values were decreased and a* values were increased in pizza dough/baked pizza with OSP (2, 3.4, and 5%) 26 or bread with fried/dried/unprocessed OSP. 27 Thus, as the phenolic concentration was increased, the significant decrease in the L* value (indicating darker color) may be related with the intense Maillard reactions or the dominant color of the phenolic source present in the crackers cooked at high temperatures and with a large surface area.…”
Section: Nutritional Value and Color Of Functional Crackerssupporting
confidence: 88%
“…This is also a common phenomenon when replacing gluten with fiber. This process is understood as being the result of prolonged gluten hydration and starch gelatinization (Yeom et al, 2017).…”
Section: Baking Lossmentioning
confidence: 99%
“…It has been shown that the by-products contain more bioactive compounds compared to the edible part. The bulb part of the onion is mainly consumed, and the amount of peel and root that is discarded continues to increase [15]. Therefore, there is a need to explore ways to utilize these by-products, but so far, research on onions has focused on the edible part of the onion, and research on the by-products is rare.…”
Section: Introductionmentioning
confidence: 99%